Justifying Partiality - Lord, Errol (Ethical theory and moral practice, 2016)
Its an undeniable fact about our moral lives that we are partial towards certain people and projects. Despite this, it has traditionally been very hard to justify partiality. In this paper I defend a novel partialist theory. The context of the paper is the debate between three different views of how partiality is justified. According to the first view, partiality is justified by facts about our ground projects. According to the second view, partiality is justified by facts about our relationships with the things that we are partial towards. And according to the third view, partiality is justified by facts about the things that we are partial towards. I argue that all three views contain part of the truth. We can see this by adopting a more sophisticated view of the weight of reasons. Once we do this, it will be clear that both facts about individuals and facts about relationships play a role in explaining why we often have stronger reason to act well towards those things we are partial towards. Further, I argue, facts about projects help explain why facts about relationships play the role that they do in determining the strength of our reasons.